Hubungan Persepsi Benefit dengan Tingkatan Niat Ibu Balita dalam Rangka Kunjungan Penimbangan Balita di Posyandu - Dwi Risky Arini; Syamsul Arifin; Ida Yuliana (Homeostasis, 2018)
Abstract: Malnutrition is responsible for one-third of all childhood dead causes worldwide. Government steps to early detect nutritional status is by weigh visitation program in posyanduThe purpose of this study is to analyze the correlation between benefit perception to the children under-five years mother level of intention in order to weigh their child in Children and Health Maternal Service of Pekapuran Raya Public Health Center working area. Research method is analytical observational with cross-sectional approach. The number of sample is 50 respondents used purposive sampling technique. Data were analyzed by using somers'd test with 95% confidence level. The results showed benefit perception of low are 2%, moderate are 24% and high are 74%. Mother's intention level with criteria of low are 2%, moderate are 56% and strong are 42%. The result of the somers'd test showed the value of p = 0,000 and the value of r = 0.533. In conclusion, there is positivet relationship with the moderate correlation between the benefit perception with children under five years mother intention level to weigh their children in posyandu. Keywords: benefit perception, intention, children under five years weigh, maternal and child health service Abstrak: Kurang gizi menjadi penyebab sepertiga dari seluruh penyebab kematian anak di seluruh dunia. Langkah pemerintah untuk deteksi dini status gizi melalui program kunjungan penimbangan di posyandu. Tujuan penelitian ini untuk menganalisis hubungan persepsi benefit dengan tingkatan niat ibu balita dalam kunjungan penimbangan balita di posyandu wilayah kerja Puskesmas Pekapuran Raya. Metode penelitian observasional analitik dengan pendekatan cross-sectional. Besar sampel 50 responden menggunakan teknik purposive sampling. Data dianalisis menggunakan uji Somers’d dengan tingkat kepercayaan 95%. Hasil penelitian menunjukan persepsi benefit kriteria rendah 2%, sedang 24% dan tinggi 74%. Tingkatan niat ibu balita kriteria lemah 2%, sedang 56% dan kuat 42%. Hasil uji Somers’d menunjukan nilai p=0,000 dan nilai r=0,533. Kesimpulan penelitian ini terdapat hubungan positif dengan korelasi cukup antara persepsi benefit dan tingkatan niat ibu balita menimbang balita. Kata-kata kunci: persepsi benefit, niat, penimbangan balita, posyandu